Programa viver sem cárie: relato de 15 anos de experiência - Pinto, Alana Barbosa Alves [UNESP]; França, Mariana Oliveira [UNESP]; Lemos, Letícia Vargas Freire Martins [UNESP]; Ramos, Carolina Júdica [UNESP]; Myaki, Silvio Issao [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to present the results of 15 years of the extension project of Dentistry for Babies from ICT / SJC - UNESP, Living Without Caries Program. The methodological difference is the dental education of the mother occurs before the baby's first appointment. The treatment protocol is characterized by three stages: educational lecture for pregnant between the 6th and the 8th month of pregnancy; the first dental appointment of the baby occurs between the 4th and the 6th month of life; dental appointment (return every 4 months) until the child reaches 48 months of age. The service is carried out by graduate students, dentists and supervised by teachers. The results (period between 2001 to 2015) found that of 260 children who joined the program, 120 were followed until they are 12 months; 42 to 24 months; 28 to 36 months and 65 to 48 months. 75 children followed up to 36 months and 48 months completed the development of the primary dentition without caries lesions and 18 developed carious lesions. The failure factors, alone or combined, were: the lack or neglect oral hygiene habits at home; uncontrolled eating habits and not attendance to the program. We concluded that the consolidation of the program or the absence of the development of caries is linked to the rational use of sugars, oral hygiene habits and attendance to the program.

O objetivo deste trabalho foi apresentar os resultados de 15 anos do projeto de extensão universitária de Odontologia para Bebês do ICT/SJC – UNESP, Programa Viver Sem Cárie. O diferencial metodológico consiste na educação odontológica da gestante que antecede a primeira consulta do bebê. O protocolo de atendimento caracteriza-se por três etapas: palestra educativa para gestante entre o 6º e o 8º mês gestacional; primeira consulta do bebê entre o 4º e o 6º mês de vida; consultas odontológicas do bebê (retorno a cada 4 meses), até a criança completar 48 meses de idade. As diretrizes clínicas obedecem às normas oficiais. O atendimento é realizado por alunos de graduação e profissionais; coordenado por docentes do Programa. Os resultados são referentes ao período entre 2001 a 2015 e revelaram que das 260 crianças que aderiram ao programa, 120 foram acompanhadas até completarem 12 meses; 42 até 24 meses; 28 até 36 meses e 65 até 48 meses. Das crianças acompanhadas até 36 e 48 meses, 75 completaram o desenvolvimento da dentição decídua sem estabelecimento de cárie e 18 desenvolveram lesões cariosas. Dentre os fatores de insucesso, isoladamente ou associados, destacam-se: falta ou descuido nos hábitos de higiene bucal domiciliar; descontrole dos hábitos alimentares e não assiduidade. Assim conclui-se que a consolidação do programa, ou seja, a ausência do desenvolvimento de lesões de cárie está associada ao uso racional dos açúcares, instituição de hábitos de higiene bucal e assiduidade ao programa.
Keywords: Pediatric dentistry; Dental caries; Prevention & control; Odontopediatria; Cárie dentária; Prevenção & controle